Kebijakan Kriminal Terhadap Tindak Pidana Perzinahan Berdasarkan Hukum Pidana Positif dan Hukum Pidana Islam - Pratama, Raka Indra; Mahmud, Ade; Zakaria, Chepi Ali Firman (Al-Jinayah : Jurnal Hukum Pidana Islam, 2022)
Abstracts: The criminal policy against the crime of adultery in the Positive Criminal Law is contained in Article 284 of the Criminal Code, which criminalizes anyone who has sexual intercourse if one of the perpetrators or both of them is married. Adultery in this article is not comprehensive and fulfills a sense of justice for some people who think that adultery is not limited to that because it is not following the values ​​of the Indonesian people's customs and Islamic law, in which the majority of Indonesian people are Muslims. The Criminal Policy in the RKUHP includes an expansion of the meaning of adultery which criminalizes a person who commits adultery with the unconditional condition that one of the perpetrators or both of them is married, the RKUHP also includes cohabitation adultery and incestuous adultery (family ties). This writing does not only make a comparison between the criminal policies regulated in the Positive Criminal Law, namely Article 284 of the Criminal Code and the RKUHP, with Islamic Criminal Law. the problem of poverty which causes prostitution activities to still occur and religious marriage activities that are not registered by the state are carried out by some Indonesian people. Keywords: Islamic Criminal Law, Criminal Policy, Adultery